Women and Technological Change in Nineteenth Century Montreal - Bradbury, Bettina (Women, Work and Place, 1994)
Keywords: Femmes

Working Families: Age, Gender and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Labour / Le travail, 1994)
Keywords: Famille; Femmes

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail